PENGARUH STRATEGI PEMBELAJARAN HEURISTIK VEE TERHADAP KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI KEMAMPUAN AWAL SISWA KELAS IX SMPN SATU ATAP 12 SAROLANGUN - Karyanti (Mat-Edukasia, 2020)
Based on the initial test results there are 4 indicators of problematic mathematical reasoning abilities. This study aims to determine and describe the mathematical reasoning ability using the heuristic vee learning strategy in terms of initial abilities better than conventional learning of class IX students of One Roof 12 Sarolangun school year 2019/2020. This study uses a quantitative approach. The method used is an experimental method with a 2 x 3 factorial design involving 2 classes as samples. Sampling using simple random sampling technique. The instrument used in this research is a mathematical reasoning test in the form of description. From the analysis concluded: Hypothesis 1. Mathematical reasoning ability using vee heuristic learning strategies is better than conventional learning Hypothesis 2 Mathematical reasoning ability of students with high initial ability using vee heuristic learning strategies is no better than conventional learning, Hypothesis 3 Mathematical reasoning ability of students with initial ability is using vee heuristic learning strategy better than conventional learning, Hypothesis 4 Mathematical reasoning ability of students with low initial ability to use vee heuristic learning strategy is no better than conventional learning, Hypothesis 5 There is no interaction between vee heuristic learning strategy and conventional learning on ability mathematical reasoning in terms of initial ability.